Cytologic appearance of retinal cells included in a fine‐needle aspirate of a meningioma around the optic nerve of a dog. (8th May 2013) - Tvedten, Harold; Hillström, Anna
Abstract A 6‐year‐old Wirehair Dachshund had a meningioma around the optic nerve that caused exophthalmos. A benign mesenchymal tumor was suspected based on the cytologic pattern of a fine‐needle aspirate, and a meningioma was diagnosed by histopathologic examination. In addition to the meningioma cells, the cytologic smears included groups of cells from apparently 4 layers of normal retina. In particular, uniform rod‐shaped structures in the cytologic sample could suggest rod‐shaped bacteria, but these structures were identified as cylindrical outer segments of photoreceptor rod cells. Other retinal structures recognized included pigmented epithelial layer cells with their uniquely formed pigment granules, the characteristic bi‐lobed, cleaved nuclei from the outer nuclear layer, and nerve tissue likely from the outer plexiform layer of the retina.